On the optimal planning of a hydrogen refuelling station participating in the electricity and balancing markets. (6th January 2021) - Dadkhah, Akbar; Bozalakov, Dimitar; De Kooning, Jeroen D.M.; Vandevelde, Lieven
Abstract: This paper presents an optimisation model to assess the techno-economic feasibility of a hydrogen refuelling station, which purchases power from the electricity market, supplies the mobility sector with hydrogen, and participates in the ancillary service market. The problem is formed as a mixed-integer nonlinear programming model to investigate the optimal operational plans considering the nonlinear behaviour of an electrolyser and grid costs calculation model. Obtained results from various scenarios in 2020 and 2030 show that participation in the reserve market considering optimal sizing and dispatch of components increase revenues up to 16%, and as a result, decrease the hydrogen break-even price by up to 4.7% and 6.4% in 2020 and 2030, respectively. Exemption from tax and levies for connection to the grid reduces the hydrogen break-even price by up to 13%. Plant operators could benefit from the proposed approach to schedule components reliably while meeting the hydrogen demand and maximising the annual profits. Graphical abstract: Image 1 Highlights: Techno-economic model of an HRS able to inject hydrogen into the gas grid. Optimal sizing and operation of an HRS in energy and ancillary services markets. The nonlinear model of the electrolyser and grid costs components. Determining the minimum hydrogen price for profitable business cases. Selling hydrogen to vehicles together with optimal reserve provision is preferred.